Dose and time effect of CdTe quantum dots on antioxidant capacities of the liver and kidneys in mice - Wang, Jilong (Int J Nanomedicine, 2017)
Although quantum dot (QD)-induced toxicity occurs due to free radicals, generation of oxidative stress mediated by reactive oxygen species (ROS) formation is considered an important mechanism. However, free radical mechanisms are essentially difficult to elucidate at the molecular level because most biologically relevant free radicals are highly reactive and short-lived, making them difficult to directly detect, especially in vivo. Antioxidants play an important role in preventing or, in most cases, limiting the damage caused by ROS. Healthy people and animals possess many endogenous antioxidative substances that scavenge free radicals in vivo to maintain the redox balance and genome integrity. The antioxidant capacity of an organism is highly important but seldom studied. In this study, the dose and time effects of CdTe QDs on the antioxidant capacities of the liver and kidneys were investigated in mice using the electron paramagnetic resonance (EPR) spin-trapping technique. We found that the liver and kidneys of healthy mice contain specific antioxidant capacities that scavenge ·OH and ·O(2)(−). Furthermore, oxidative stress markers (superoxide dismutase [SOD], catalase [CAT], glutathione peroxidase [GPx], glutathione [GSH] and malondialdehyde [MDA]) were examined. In dose course studies, the free radical scavenging efficiencies of the liver and kidneys were found to gradually decrease with increasing concentration of CdTe QD exposure. The activities and levels of SOD, CAT, GPx and MDA were observed to increase in treated groups, whereas those of GSH were reduced. The time course studies revealed that the QD-induced antioxidant efficiency reduction was time dependent with GSH decrease and could recover after a period of time. These experimental results offer new information on QD toxicity in vivo. Specifically, CdTe QDs can deplete GSH to reduce the elimination ability of the liver and kidneys for ·OH and ·O(2)(−), thus inducing oxidative damage to tissues.